Evaluation of two commercial immunochromatographic rapid tests for detection of IgM antibodies against leptospires in human serum - Ramli, Siti Nur Alia (2018)
Leptospirosis is a zoonotic disease which shows the increasing cases over the recent years. In Malaysia, leptospirosis became a notifiable disease in 2011. The treatment of leptospirosis is not difficult, however, the diagnosis is a big challenge. Leptospirosis is a biphasic infection, where the first phase (acute or septic phase) is from 3 to 7 days and followed by the second phase that happens from 7 to 14 days. The patients are mostly asymptomatic in the first few days. During infection, the bacteria can be found in the blood. Then, it moves to kidney and starts shedding in the urine. Antibodies start to develop into detectable amount during the second phase. Diagnosis of leptospirosis involves testing for the presence of bacteria or their DNA in the first phase and antibodies in the second phase. Since the actual onset of illness is not clear, laboratory diagnosis should include both microbiological and serological tests. Clinical diagnosis is another big challenge as the symptoms are similar to several febrile illnesses in the tropics. However, clinical suspicion and positive laboratory investigation are very important to start the therapy. The microbiological examination involves culturing the bacteria and PCR based detection which needs DNA from the clinical samples. However, microbiology is not useful for rapid and early diagnosis as Leptospira needs minimum 2 to 4 weeks to grow, while PCR needs DNA extraction, technical ies, and expensive PCR machines and reagents. In the context of serology, microscopic agglutination test, which is the gold standard, is technically tedious as well as the interpretations are very subjective. Most importantly, it also requires a large of live cultures. From the hospital point of view, a rapid test, which at least be able to give a laboratory indication, will be sufficient to direct the treatment options. Many hospitals do not have the facilities to perform MAT or PCR and the assays ; moreover, will take few days. To date, there are several commercial rapid tests which detect IgM specific to Leptospira antigens. The sensitivity and specificity of those tests vary geographical regions. The present study was aimed at evaluating the diagnostic accuracy of two rapid tests namely Leptocheck-WB (Zephyr Biomedicals, India) and ImmuneMed IgM Duo Rapid (IMMUNEMED, Inc Korea) for detection of acute leptospirosis in human.The study used two approaches namely prospective and retrospective evaluation to determine the diagnostic accuracy in the two rapid tests. In the prospective approach, the evaluation was performed on clinically suspected leptospirosis patients from a single hospital and used MAT and qPCR as the reference test. The accuracy of Serion ELISA classic also had been evaluated and results of diagnostic accuracy were compared to Leptocheck-WB and ImmuneMed IgM Duo Rapid. In the retrospective approach, the confirmed leptospirosis positive samples were obtained from the Public Health Laboratory Kota Bharu. The samples were evaluated and used only MAT results as the reference test. In the prospective evaluation, among the 50 blood samples tested from clinically suspected leptospirosis cases, six were positive MAT and 13 were positive qPCR. The Leptocheck-WB showed sensitivity and specificity of 47.3% and 80.65% respectively. ImmuneMed IgM Duo Rapid showed sensitivity and specificity of 15.79% and 90.32% respectively. The results of sensitivity and specificity of Leptocheck-WB and ImmuneMed IgM Duo in prospective evaluation samples were compared to the result from Serion ELISA classic. Serion ELISA classic showed 26.32% sensitivity and 83.87% specificity. For retrospective samples, Leptocheck-WB showed sensitivity and specificity of 90.72% and 76.32% respectively. ImmuneMed IgM Duo Rapid showed sensitivity and specificity of 40.21% and 89.47 respectively. In conclusion, from the present study for both prospective and retrospective samples, Leptocheck- WB was found to be more sensitive in detecting acute leptospirosis in human while ImmuneMed IgM Duo Rapid was found to be more specific in detecting acute leptospirosis.